Common variable immunodeficiency: An uncommon cause of bronchiectasis, granulomatous disease, chronic liver disease, and enteropathy – Case report and review of literature - Veena Shamsudeen; Arun Hegde; Uday Bhanu Kovilapu; Nisha Verma; Anurag Jain (Indian Journal of Rheumatology)
Common variable immune deficiency (CVID) is a primary immunodeficiency syndrome, characterized by a defective B cell function. Although there is no age or gender predilection, it is usually diagnosed between the second and fourth decades of life. The clinical features are diverse and include recurrent infections and autoimmune and granulomatous diseases, along with an increased risk of malignancies. Respiratory involvement occurs commonly in the form of recurrent upper and lower respiratory tract infections (LRTI), at times resulting in bronchiectasis. Gastrointestinal involvement may manifest either in the form of an infectious diarrhea due to parasites such as Giardia lamblia and bacteria such as Campylobacter jejuni, or as a noninfectious enteropathy resembling coeliac disease or inflammatory bowel disease. Some patients develop a granulomatous disease manifesting with noncaseating granulomas, especially of lymph nodes, skin, lung, spleen, and liver. Nearly 20%–25% of cases develop autoimmune complications such as autoimmune hemolytic anemia and immune thrombocytopenia. Hepatic involvement can occur in the form of abnormal biochemistry, nodular degenerative hyperplasia, and cirrhosis of liver. Treatment of infection, and replacement of immunoglobulins, remains the mainstay of management of CVID. Herein, we describe the case of a 48-year-old female, who initially presented to our hospital with recurrent bouts of upper and LRTI, along with small-bowel diarrhea, and progressively developed generalized lymphadenopathy and ascites, before being finally diagnosed by the rheumatologist, as a case of CVID, with associated CVID-related enteropathy, granulomatous disease, and chronic liver disease. She was managed with immunoglobulin replacement therapy, along with hydroxychloroquine and steroids with good response.